Migrant and Refugee Background Students Learning Through Play - Ferreira, Jonathan; Kendrick, Maureen; Early, Margaret (The Reading teacher, 2022)
With the unprecedented increase of forced displacement in recent years, there has been a growing concern with how children from migrant and refugee backgrounds adjust to resettlement in Western schools. Adopting a sociocultural approach to science education, the authors explore how scientific concepts related to the water cycle and practices such as modelling are realized multimodally through play. By means of two constructive and imaginative play activities, block building and scrapbook making, illustrative examples showcase how four children from migrant and refugee backgrounds repurposed various multimodal resources to make sense of scientific concepts, use scientific language, and problem solve in relation to their life experiences beyond the classroom. Implications encourage teachers to consider designing content‐area language instruction infused with play‐based activities to give rise to alternative avenues through which emerging bi/multilingual learners can take risks, be engaged cognitively, and apply their new knowledge creatively.